Behavioral, Immunologic, and Virologic Correlates of Oral Human Papillomavirus Infection in HIV-Infected Youth. Issue 5 (May 2015) - Kahn, Jessica A.; Rudy, Bret J.; Xu, Jiahong; Secord, Elizabeth A.; Kapogiannis, Bill G.; Thornton, Sarah; Gillison, Maura L.
<x xml:space="preserve">Abstract</x> Background Little is known about the epidemiology or risk factors for oral human papillomavirus (HPV) in HIV-infected youth. The objectives of this study were to determine the prevalence and correlates of oral HPV infection and to explore the association between HPV vaccination and oral infection in HIV-infected youth. Methods Youth 12 to 24 years of age with behaviorally acquired HIV were recruited for this cross-sectional study. Procedures involved medical chart review, survey, and collection of an oral rinse sample. Univariable and multivariable logistic regression models were used to determine whether demographic, behavioral, immunologic, and virologic factors and history of vaccination were significantly associated with oral HPV infection. Results Mean age of the 272 participants was 21.5 years; 64% were non-Hispanic black and 20.2% were Hispanic; and 10.8% of men compared with 20.3% of women were fully vaccinated. Human papillomavirus prevalence was 19.7% in men and 18.6% in women (P = 1.0). Only men were positive for vaccine-type HPV: 5.6% were positive for HPV-6, HPV-11, HPV-16, and/or HPV-18, and 4.2% were positive for HPV-16 and/or HPV-18. Among men who were fully vaccinated, none were positive for HPV-6, HPV-11, HPV-16, and/or HPV-18, compared with 12 (6.3%) of men who were not fully vaccinated (P = 0.37). Two variables were marginally associated with oral HPV (P < 0.10): marijuana use in the previous 3 months and lower CD4+ T-cell count. Conclusions Prevalence rates of oral HPV were relatively high in this population of HIV-infected youth and were similar in male and female youth. No fully vaccinated men were infected with vaccine-type HPV.